Trends in the evolution of intronless genes in Poaceae - Chen, Yong; Ma, Ting; Zhang, Tingting; Ma, Lei (Frontiers in Plant Science, 2023)
Intronless genes, which are a feature of prokaryotes, are a fascinating group of genes that are also present in eukaryotes. In the current study, a comparison of Poaceae genomes revealed that the origin of intronless genes may have involved ancient intronic splicing, reverse transcription, and retrotranspositions. Additionally, intronless genes exhibit the typical features of rapid evolution, including recent duplications, variable copy numbers, low divergence between paralogs, and high nonsynonymous to synonymous substitution ratios. By tracing intronless gene families along the phylogenetic tree, we determined that the evolutionary dynamics of intronless genes differed among Poaceae sub-families. Intronless gene families developed rapidly before the divergence of Pooideae and Oryzoideae and expanded slowly after the divergence. In contrast, they emerged gradually and consistently in the Chloridoideae and Panicoideae clades during evolution. Furthermore, intronless genes are expressed at low levels. Under relaxed selection pressure, retrotranspositions, intron loss, and gene duplications and conversions may promote the evolution of intronless genes. The comprehensive characterization of intronless genes is critical for in-depth studies on intron functions and evolution as well as for assessing the importance of introns in eukaryotes.